Dyeing properties of cationized and non-cationized cotton fabrics dyed with Vitis vinifera L. leaves extract. Issue 4 (2nd April 2016) - Rym, Mansour; Farouk, Mhenni; Bechir, Ezzili M.
Abstract : This study lays bare two main objectives. The first is to determine the amount of anthocyanins in the leaves of Vitis vinifera L. by the spectrophotometric method and the second is to dye cationized and non-cationized cotton fabrics with the V. vinifera L. leaves aqueous extract. We have thoroughly investigated the effects of dye bath pH and temperature on the dyeing proprieties of the aforementioned fabrics. The color strength ( K / S value) of dyed cationized cotton fabrics ( K / S = 12) has been better than the non-cationized ones ( K / S = 4). Experimental results show that the fastness properties of dyed cationized cotton fabrics range from average to good. We find that the cationization of cotton fabrics has largely improved the dyeability and fastness properties of cotton fabrics dyed with V. vinifera L. leaves aqueous extract.